Review of lateral epitaxial overgrowth of buried dielectric structures for electronics and photonics. (May 2021) - Ironside, Daniel J.; Skipper, Alec M.; García, Ashlee M.; Bank, Seth R.
Abstract: Integration of embedded dielectric structures with crystalline III-V materials has generated significant interest, due to a host of important applications and material improvements that are central to high performance optoelectronic devices. The core challenge is the production of high-quality crystalline layers grown above embedded dielectric materials, requiring the growth processes of both lateral epitaxial overgrowth (LEO) and coalescence. In this review article, we provide a detailed and up-to-date description of the recent advances in both LEO and coalescence in III-V materials, from its extension to molecular beam epitaxial growth and high-quality coalescence in InP and GaAs to emerging applications that utilize encapsulated air voids to enhance optical devices. We also explore the epitaxial integration of other materials, particularly metals, with III-V semiconductors.